A deterministic river temperature model to prioritize management of riparian woodlands to reduce summer maximum river temperatures. Issue 8 (12th August 2021) - Jackson, Faye L.; Hannah, David M.; Ouellet, Valerie; Malcolm, Iain A.
Abstract: Increasing river temperatures are a threat to cold water species including ecologically and economically important freshwater fish, such as Atlantic salmon. In 2018, ca. 70% of Scottish rivers experienced temperatures which cause thermal stress in juvenile salmon, a situation expected to become increasingly common under climate change. Management of riparian woodlands is proven to protect cold water habitats. However, creation of new riparian woodlands can be costly and logistically challenging. It is therefore important that planting can be prioritized to areas where it is most needed and can be most effective in reducing river temperatures. The effects of riparian woodland on channel shading depend on complex interactions between channel width, orientation, aspect, gradient, tree height and solar geometry. Subsequent effects on river temperature are influenced by water volume and residence time. This study developed a deterministic river temperature model, driven by energy gains from solar radiation that are modified by water volume and residence time. The resulting output is a planting prioritization metric that compares potential warming between scenarios with and without riparian woodland. The prioritization metric has a reach scale spatial resolution, but can be mapped at large spatial scales using information obtained from a digital river network. The results indicate that water volume and residence time, as represented by river order, are a dominant control on the effectiveness of riparian woodland in reducing river temperature. Ignoring these effects could result in a sub‐optimal prioritization process and inappropriate resource allocation. Within river order, effectiveness of riparian shading depends on interactions between channel and landscape characteristics. Given the complexity and interacting nature of controls, the use of simple universal planting criteria is not appropriate. Instead, managers should be provided with maps that translate complex models into readily useable tools to prioritize riparian tree planting to mitigate the impacts of high river temperatures. Abstract : This study developed a deterministic river temperature model driven by energy gains from solar radiation, modified by water volume and residence time. Solar radiation varied with channel shading in response to channel width, orientation, aspect, gradient and tree height. A planting prioritisation metric was developed by comparing scenarios with and without riparian woodland to identify where trees can most effectively reduce summer temperatures. This metric can be mapped nationally, with a reach scale resolution and used to guide planting.